CT or MR Enterography to Assess Response During Vedolizumab Therapy for Small Bowel Crohn's Disease. Issue 1 (3rd February 2022) - Kwapisz, Lukasz; Bruining, David H; Inoue, Akitoshi; Lee, Yong S; Edwards, Phillip K; Holmes, David R; Carter, Rickey E; Siegelman, Jenifer; Fletcher, Joel G
Abstract: Background: To describe response to therapy of small bowel (SB) Crohn's disease (CD) at CT or MR enterography (CTE/MRE) in patients on vedolizumab. Methods: Patients with SB CD who underwent CTE/MRE exams greater than 12 months apart on vedolizumab therapy were included. Length (in cm) and inflammation severity (EMBARK score) of inflamed SB segments were assessed. Changes in inflammation length of 3.4 cm or greater or inflammation severity of 2 EMBARK points or greater was categorized as response or progression, as appropriate, with development of newly inflamed segments, strictures, or penetrating complications also indicating progression. Patients not meeting the criteria for response or progression were categorized as having stable disease. Results: Of 36 SB CD patients, the large majority had prior surgery (86%; 31), anti-TNF use (92%; 33), and internal penetrating (78%; 28) disease. Thirty-two patients had paired baseline and follow-up CTE/MRE exams without interval surgery, with clinical response observed in 24/32 (75%). Based on imaging response criteria, 22% (7/32; 95% CI: 9%–40%) had response, 50% (16/32; 95% CI: 32%–68%) were stable, and 28% (9/32; 95% CI: 14%–47%) had disease progression. Fifty-six percent of (18/32; 95% CI: 38%–74%) patients had clinical improvement with response or stable disease by imaging. Patients with stable disease had shorter median baseline lengths of SB inflammation ( P = .012). Proportion of patients with colonic inflammation, perianal disease, or penetrating complications did not change. Conclusions: Most patients on vedolizumab for over 12 months demonstrated response or stable SB disease when using objective cross-sectional radiologic imaging criteria using CTE/MRE. Lay Summary: Most Crohn's disease patients who stayed on vedolizumab for over 12 months demonstrated improved or stable small bowel disease when evaluating follow-up CT or MR enterography exams for changes in small bowel inflammation, or newly developed strictures or penetrating complications.